Clinical utility of a rapid 'on-demand' laboratory-based SARS-CoV-2 diagnostic testing service in an acute hospital setting admitting COVID-19 patients. (November 2021) - Yau, Fiona; Ferreira, Rosalina; Kamali, Rima; Bird, Paul W.; Halliwell, Richard; Patel, Hemu; Nicoara, Daniela C.; Woltmann, Gerrit; Tang, Julian W.
Highlights: Rapid diagnostic testing for COVID-19 can improve patient flow and reduce nosocomial transmission. The setting was an acute respiratory ward in a busy teaching hospital managing COVID-19 patients. A rapid COVID-19 testing facility in a nearby satellite laboratory was set up to support this ward on the same site. Rapid PCR-based assays were used that could test 4–8 samples in parallel, each taking 50–80 min to complete. This rapid test facility was successful in improving patient flow to downstream COVID-19 and non-COVID-19 wards. Abstract: Background: With the onset of the COVID-19 pandemic in 2020, hospital clinical teams have realised that there is a need for a rapid, accurate testing facility that will allow them to move patients quickly into isolation rooms or specific COVID-19 cohort wards as soon as possible after admission. Methods: Starting from July 2020, PCR-based test platforms, which could test 4–8 samples in parallel with turnaround (sample-to-result) times of 50–80 min, were placed in a satellite laboratory. This laboratory was on the same floor and within walking distance to the acute respiratory admissions ward. It was staffed by a team of three mid-Band 4 staff that split a 0700–2200 h-work day, 7 days a week, with 2 senior supervisors. Urgent sample testing was decided upon by the clinical teams and requested by phone. The test results were entered manually in real-time as they became available, and sent electronically to the requesting ward teams. Results: The daily/monthly PCR positive test numbers approximately followed the local and national UK trend in COVID-19 case numbers, with the daily case numbers being reflective of the November and December 2020 surges. Test results were used to rapidly segregate positive patients into dedicated COVID-19 ward areas to minimise risk of potential nosocomial transmission in crowded waiting areas. Testing capacity was sufficient to include cases with uncertain diagnosis likely to require hospital admission. Following completion of other admission processes, based on these rapid test results, patients were allocated to dedicated COVID-19 positive or negative cohort wards. Conclusions: This rapid testing facility reduced unnecessary 'length-of-stay' in a busy acute respiratory ward. In the current absence of a treatment for mild-to-moderate COVID-19, on which patients could be discharged home to complete, the rapid test facility has become a successful aid to patient flow and reduced exposure and nosocomial transmission.